Anionic Polymerization of 2‐Hexyl[3]dendralene. Issue 1 (11th December 2017) - Takamura, Yuki; Takenaka, Katsuhiko; Toda, Tomoyuki; Takeshita, Hiroki; Miya, Masamitsu; Shiomi, Tomoo
Abstract: In this study, the polymerization behavior of 2‐hexyl[3]dendralene (H3D ), which is an alkyl‐group‐derived [3]dendralene, is examined. The polymerization ofH3D in tetrahydrofuran (THF) at −78 °C with potassium naphthalenide as the initiator affords poly(H3D ) with a narrow molecular weight distribution, although a small shoulder peak is observed at a high molecular weight even before the monomer is completely consumed. The molecular weight distribution of poly(H3D ) prepared in heptane is broader than that prepared in THF, indicating that the nucleophilic addition of a propagating carbanion to the carbon–carbon double bond in the polymer chain occurs in addition to polymerization. Furthermore, the microstructure of poly(H3D ) is investigated by NMR. Signals corresponding to the conjugate addition structure, that is, 1, 4‐ and 4, 6‐structures, are exclusively observed. Poly(H3D ) prepared in heptane contains a higher content of the 4, 6‐structures compared with those prepared in THF. Abstract : Anionic polymerization of 2‐hexyl[3]dendralene in tetrahydrofuran (THF) gives a polymer of controlled chain structure with narrow molecular weight distribution under the appropriate polymerization condition. Only conjugate addition structures having both cis ‐ and trans ‐configuration present in the polymer chain.